[Rezension von] The visitor: André Palmeiro and the jesuits in Asia. By Liam Matthew Brockey. Cambridge, Mass.: Harvard University Press, 2014. 528 pp. ISBN 9780674416680 (cloth). - Hosne, Ana Carolina (The journal of Asian studies, 2016)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911815001722/resource/name/firstPage-S0021911815001722a.jpg